Strategi Pemerintah Kabupaten Bulukumba Dalam Mengembangkan Desa Wisata Kawasan Adat (Studi Pada Desa Wisata Kawasan Adat Ammatoa Kajang) - Fuad Arafah (Departemen Ilmu Pemerintahan Fisip Unhas, 2025)
This study aims to examine the strategy of the Bulukumba Regency Government in developing the Ammatoa Kajang Indigenous Tourism Village and to identify the supporting and inhibiting factors in the development of the tourism village. This research employed a qualitative research approach. The study was conducted in the Ammatoa Kajang Indigenous Area, Bulukumba Regency. The data used in this study consisted of primary and secondary data. Data were collected through observation, interviews, literature review, and documentation. The data were analyzed using qualitative analysis techniques. The results of the study indicate that the Bulukumba Regency Government plays a significant role in the development of the Ammatoa Kajang Tourism Village. The development efforts include the optimization of tourism information, optimization of tourism attractions, and optimization of tourism management. The optimization of tourism information is carried out through the use of tourism-related information for promotional purposes; however, its utilization has not yet been fully optimized. The optimization of tourism attractions is constrained by the absence of concrete government programs, underutilized tourism opportunities, development strategies that are not fully market-oriented, limited distribution of tourism centers, and accessibility issues that still require improvement. Community participation in Ammatoa Kajang tourism development is reflected in the community’s full involvement in managing the tourism area and producing local handicrafts, particularly traditional black woven sarongs. Nevertheless, these efforts remain limited and require greater government support to enhance community skills and capacities. Furthermore, tourism management has not been implemented optimally due to limited financial resources, as funding is largely derived from the local community, as well as the relatively low levels of knowledge and managerial skills among community members.